Autobiographical narrations of sexual harassment on online blogs as tools for Egyptian women’s empowerment: a linguistic and critical analysis - La Causa, Lucia (European Scientific Journal, ESJ, 2025)
Sexual violence against women is still a global and pervasive problem (International Institute for Global Health, 2019), especially in male-controlled countries like Egypt. These days, an increasing number of Egyptian women is using autobiographical narrations on online blogs to condemn negative ideologies and misogynist practices in their society, denouncing episodes of sexual harassment that they have experienced or witnessed. In this study, it has been observed how they use language on blogs to recount their own experiences of sexual abuse. A sample of five autobiographies retrieved from the Egyptian blog Speak Up has been selected for the purpose of this investigation. These stories have been linguistically and critically analysed through Halliday’s functional grammar (2014) and a Critical Discourse Analysis (Machin & Mayr, 2023), more specifically a Feminist Critical Discourse Analysis (Lazar, 2007), with the aim of observing how personal female identities and empowerment are performed through this form of first-person narration (Lazar, 2006; Bamberg, 2010; Schiffrin et al., 2010). A special focus has been on verbal and semiotic choices, which suggest agency, transitivity, and power relationships, and on appraisal elements which give information about the narrators’ “feelings and opinions” (Derewianka & Jones, 2016, p. 25). The analysis has proved to be useful in showing how these Egyptian women narrators consciously or unconsciously present themselves as “empowered victims”.